Long-term nitrogen retention and transit time distribution in agricultural catchments in western France. (25th November 2020) - Dupas, Rémi; Ehrhardt, Sophie; Musolff, Andreas; Fovet, Ophélie; Durand, Patrick
Abstract: Elevated nitrogen (N) concentrations have detrimental effects on aquatic ecosystems worldwide, calling for effective management practices. However, catchment-scale annual mass-balance estimates often exhibit N deficits and time lags between the trajectory of net N inputs and that of N riverine export. Here, we analyzed 40-year time series of N surplus and nitrate-N loads in 16 mesoscale catchments (104–10 135 km 2 ) of a temperate agricultural region, with the aim to (1) investigate the fate of the 'missing N', either still in transit through the soil—vadose zone—groundwater continuum or removed via denitrification, and (2) estimate the transit time distribution of N by convoluting the input signal with a lognormal model. We found that apparent N retention, the 'missing N', ranged from 45%–88% of then N net input, and that topsoil N accumulation alone accounted for ca. two-thirds of this retention. The mode of the nitrate-N transit time distribution ranged from 2–14 years and was negatively correlated with the estimated retention. Apparent retention was controlled primarily by average runoff, while the transit time mode was controlled in part by lithology. We conclude that the fate of the soil 'biogeochemical legacy', which represents much of the catchment-scale 'missing N', is in our hands, since the N accumulated in soils can still be recycled in agroecosystems.